Phosphorus-containing sulfonated polyimides for proton exchange membranes - ÇAKIR, MUSTAFA; KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (WILEY-V C H VERLAG GMBH, 2008)
Synthesis and characterization of the novel sulfonated BAPPO monomer and its use in the synthesis of a new phosphine oxide-based sulfonated polyimide are described. BTDA, 6FDA, and DDS were used as monomers in the polyimide synthesis. Sulfonated polyimide membranes were obtained by a solution thermal imidization method. The thermal behavior of the polymers was investigated by DSC and TGA. The morphological structure of the membranes was investigated by tapping-mode AFM. The proton conductivities of the sulfonated polyimide increased regularly as a function of sulfonated diamine content. The conductivities are good compared to typical proton exchange membranes.
Keywords: conducting polymers; fuel cells; PEM; phosphine oxide; polyimides; COPOLYMERS; IONOMERS; ETHER); ACID